The effect of stock bonus issue announcements on Singapore share prices : implications on market efficiency - Kan, Piek Yu (2014)
The aim of this project is to test the semi-strong form of market efficiency in the Singapore context with respect to the announcement of stock bonus issues. This study attempts to seek answers to the following: i) What is the share price behaviour prior to and after the public announcement of a stock bonus issue? ii) Are Singapore stocks capable of incorporating public information into the share prices? iii) Can investors make use of public announcements of bonus 1ssue to reap abnormal profits?